Updates to the RIFM Criteria Document for fragrance ingredient evaluation - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 2-propanol, 1,1′,1′,1'-(1,2-ethanediyldinitrilo)tetrakis-, CAS Registry Number 102-60-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, octyl crotonate, CAS Registry Number 22874-79-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, propenylguaethol, CAS Registry Number 94-86-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, ethyl 3-hydroxybutyrate, CAS Registry Number 5405-41-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 3-(p-tert-butylphenyl)-2-methylpropanol, CAS Registry Number 56107-04-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, ethyl 3-hydroxyhexanoate, CAS Registry Number 2305-25-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, linoleic acid, CAS Registry Number 60-33-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, β-naphthyl isobutyl ether, CAS Registry Number 2173-57-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 1,5-dimethylhexyl acetate, CAS Registry Number 67952-57-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 3-(4-methyl-3-pentenyl)-3-cyclohexene-1-carbonitrile, CAS Registry Number 68084-04-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, cyclohexaneethyl acetate, CAS Registry Number 21722-83-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 3,5,5-trimethylcyclohexanol, CAS Registry Number 116-02-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 5-methyl-2-phenyl-2-hexenal, CAS Registry Number 21834-92-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 4-heptanol, 2,6-dimethyl-,acetate, CAS Registry Number 10250-45-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, phenylacetaldehyde glyceryl acetal, CAS Registry Number 29895-73-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, cyclohexanemethanol, 2,4-dimethyl-, CAS Registry Number 68480-15-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 2,2,6-trimethylcyclohexanone, CAS Registry Number 2408-37-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, cis-4-(isopropyl)cyclohexanemethanol, CAS registry number 13828-37-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, cyclohexanone, 2-ethyl-4,4-dimethyl-, CAS registry number 55739-89-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, squalene, CAS Registry Number 111-02-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, β-guaiene, CAS Registry Number 88-84-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 3-hexene, 1,1′,''-[ethylidynestris(oxy)]tris-, (3Z, 3′Z,3"Z)-, CAS registry number 215305-10-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, methyl 3-hydroxyhexanoate, CAS Registry Number 21188-58-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 4-methyl-2-phenyl-2-pentenal, CAS Registry Number 26643-91-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 2-phenyl-2-butenal, CAS Registry Number 4411-89-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, dodecyldimethylamine oxide, CAS Registry Number 1643-20-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, tricosane, CAS Registry Number 638-67-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, methyl 2-nonenoate, CAS registry number 111-79-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 4-(isopropyl)-β-methylcyclohexanethanol, CAS Registry Number 67634-03-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, undecanol, CAS Registry Number 30207-98-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, methyl cis-5-octenoate, CAS Registry Number 41654-15-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, methyl 3-nonenoate, CAS Registry Number 13481-87-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 4-methyl-3-penten-2-one, CAS Registry Number 141-79-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, methyl 3-hexenoate, CAS Registry Number 2396-78-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 1-(1,2,3,4,5,6,7,8-octahydro-2,3,8,8-tetramethyl-2-naphthalenyl)ethanone, CAS Registry Number 54464-57-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, docosane, CAS Registry Number 629-97-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, methyl jasmonate, CAS Registry Number 1211-29-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 2-isobutyl-4-methyltetrahydro-2H-pyran-4-ol, CAS Registry Number 63500-71-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, dimyrcene, CAS Registry Number 532-87-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, methyl myristate, CAS Registry Number 124-10-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, cyclohexane, 1-ethenyl-1-methyl-2,4-bis(1-methylethenyl)-, (1R,2R,4S)-rel-, CAS Registry Number 33880-83-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, ethyl myristate, CAS Registry Number 124-06-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 2-methylpentyl 2-methylvalerate, CAS Registry Number 90397-38-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, pyrazine, methyl (methylthio)-, CAS Registry Number 67952-65-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 2-propenoic acid, 2-[1-(3,3-dimethylcyclohexyl)ethoxy]-2-methylpropyl ester, CAS Registry Number 820975-49-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, hexadecyl palmitate, CAS Registry Number 540-10-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, cyclohexane, 1-ethenyl-1-methyl-2-(1-methylethenyl)-4-(1-methylethyl)-, didehydro derivative, CAS Registry Number 68845-33-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, acetyl cedrene, CAS Registry Number 32388-55-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, butyl sulfide, CAS Registry Number 544-40-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, heneicosane, CAS Registry Number 629-94-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, ethyl palmitate, CAS Registry Number 628-97-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, sclareol, CAS registry number 515-03-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, ethyl octadecanoate, CAS Registry Number 111-61-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, cyclohexyl methyl pentanone, CAS Registry Number 4927-39-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, heptadecane, CAS Registry Number 629-78-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, hexadecane, CAS Registry Number 544-76-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, oleic acid, CAS Registry Number 112-80-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, pentadecane, CAS Registry Number 629-62-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, tetradecane, CAS Registry Number 629-59-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, nonadecane, CAS Registry Number 629-92-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, octadecane, CAS Registry Number 593-45-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, eicosane, CAS Registry Number 112-95-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessments, ethyl ricinoleate, CAS Registry Number 55066-53-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 4-methyl-8-methylenetricyclo[3.3.1.(3,7)]decan-2-yl acetate, CAS Registry Number 122760-85-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, phytyl acetate, CAS Registry Number 10236-16-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, [2,2-bis[(3,7-dimethyl-2,6-octadienyl)oxy]ethyl]benzene, CAS Registry Number 67634-02-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 2,3,5,6-tetramethylpyrazine, CAS Registry Number 1124-11-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, cedryl methyl ether, CAS Registry Number 67874-81-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, methyl 2-(formylamino)benzoate, CAS Registry Number 41270-80-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, naphtho[2,1-b]furan, dodecahydro-3a,6,6,9a-tetramethyl-, (3aR,5aS,9aS,9bR)-, CAS Registry Number 6790-58-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, laurel leaf oil, CAS Registry Number 8007-48-5, RIFM ID 476-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, (Z)-2-penten-1-ol, CAS Registry Number 1576-95-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 6-methyl-3,5-heptadien-2-one, CAS Registry Number 1604-28-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, isopropylphenylbutanal, CAS Registry Number 125109-85-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, methyl cinnamate, CAS Registry Number 103-26-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, lovage leaf oil, CAS Registry Number 8016-31-7, RIFM ID 813-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, β,β,3-trimethyl benzenepropanol, CAS Registry Number 103694-68-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, dihydro-β-ionone, CAS registry number 17283-81-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 3-hexanone, CAS Registry Number 589-38-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, ethyl methylphenylglycidate, CAS Registry Number 77-83-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, dihydro-α-ionone, CAS Registry Number 31499-72-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, hinoki root oil, CAS Registry Number 91745-97-0, RIFM ID 5487-A2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, isobornyl methyl ether, CAS Registry Number 5331-32-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, ethyl safranate, CAS registry number 35044-57-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, Bucchu oil, betulina, CAS Registry Number 68650-46-4, RIFM ID 73-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, ethyl pyruvate, CAS registry number 617-35-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, thyme oil, red, CAS Registry Number 8007-46-3, RIFM ID 471.E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 2-methyl-3-tolylpropionaldehyde, CAS Registry Number 41496-43-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, dihydrocarvyl acetate, CAS Registry Number 20777-49-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 3,7-dimethyl-2,6-nonadien-1-al, CAS Registry Number 41448-29-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, isopulegyl acetate, CAS Registry number 57576-09-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, anisyl alcohol, CAS Registry Number 105-13-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, bicyclo[3.1.0]hexan-3-one, 4-methyl-1-(1-methylethyl)-, CAS Registry Number 1125-12-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 6-isopropyl-2(1H)-octahydronaphthalenone, CAS Registry Number 34131-98-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, ethyl 3-phenylglycidate, CAS Registry Number 121-39-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, citral, CAS Registry Number 5392-40-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 1,6-octadien-3-ol, 3,7-dimethyl-, acid-isomerized, CAS Registry Number 73018-51-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, 1,1-dimethoxycyclododecane, CAS Registry Number 950-33-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 2-ethyl-5-methoxybicyclo[2.2.1]heptane, CAS registry number 122795-41-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM natural complex substance (NCS) fragrance ingredient safety assessment, styrax absolute, CAS registry Number 8024-01-9, RIFM ID 6877.K2.1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, α,α-dimethyl-p-ethylphenylpropanal, CAS Registry Number 67634-15-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

RIFM fragrance ingredient safety assessment, α-hexylcinnamaldehyde, CAS Registry Number 101-86-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, γ-octalactone, CAS Registry number 104-50-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 4-methoxybenzoic acid, CAS Registry Number 100-09-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, 3-methyl-2-butenyl acetate, CAS Registry Number 1191-16-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, γ-hexalactone, CAS Registry Number 695-06-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, myristic acid, CAS Registry Number 544-63-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, isobutyric acid, CAS Registry Number 79-31-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, γ-decalactone, CAS Registry Number 706-14-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, γ-undecalactone, CAS Registry Number 104-67-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, isovaleric acid, CAS Registry Number 503-74-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

Update to RIFM fragrance ingredient safety assessment, γ-nonalactone, CAS Registry Number 104-61-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2026)

2nd update to RIFM fragrance ingredient safety assessment, 3,7-dimethyl-1,6-nonadien-3-ol, CAS Registry Number 10339-55-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

2nd update to RIFM fragrance ingredient safety assessment, linalool, CAS Registry number 78-70-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2H-indeno[4,5b] furan, decahydro-2,2,6,6,7,8,8-heptamethyl, CAS Registry Number 476332-65-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, γ-dodecalactone, CAS Registry Number 2305-05-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, palmitic acid, CAS Registry number 57-10-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2,6,8-trimethylnonan-4-one, CAS Registry Number 123-18-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methylbutyric acid, CAS Registry number 116-53-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4,8-dimethyl-4,9-decadienal, CAS Registry number 71077-31-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, cedrene, CAS Registry Number 11028-42-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 5-methyl-3-heptanone, CAS Registry Number 541-85-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM natural complex substance (NCS) fragrance ingredient safety assessment, iris pallida oil, CAS registry number 8002-73-1, RIFM ID 265.A2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 8H-indeno(4,5-B)furan,2,3,3a,4,5,5a,6,7,8a,9-decahydro-2,6,6,7,8,8-hexamethyl mixture of isomers, CAS Registry Number 338735-71-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-nonanone, CAS Registry Number 821-55-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-undecanone, CAS Registry Number 112-12-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-octanone, CAS registry number 106-68-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-decanone, CAS Registry Number 693-54-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-heptanone, CAS Registry Number 110-43-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, γ-heptalactone, CAS Registry Number CAS # 105-21-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, γ-valerolactone, CAS Registry Number 108-29-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, lauric acid, CAS Registry Number 143-07-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-octanone, CAS Registry Number 111-13-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, benzoin infusion, Sumatra, CAS Registry Number 9000-05-9, RIFM ID 104-K2.31 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4-heptanone, CAS Registry Number 123-19-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-heptanone, CAS Registry Number 106-35-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, myrtenol, CAS Registry Number 515-00-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-phenylpropionic acid, CAS registry number 501-52-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, hexyl phenylacetate, CAS Registry Number 5421-17-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, methyl cyclohexadiene (mixture of isomers), CAS Registry Number 30640-46-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, decanoic acid, CAS Registry Number 334-48-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 5-methyl-5-propyl-2-(1-methylbutyl)-1,3-dioxan, CAS Registry Number 80480-24-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, octanoic acid, CAS Registry Number 124-07-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Corrigendum to “RIFM fragrance ingredient safety assessment, 1,3,5-undecatriene, CAS Registry Number 16356-11-9” [Food Chem. Toxicol. (2024 Mar) 183 Suppl 1 114303. doi: 10.1016/j.fct.2023.114303. Epub 2023 Dec 4] - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, p-isopropylacetophenone, CAS Registry Number 645-13-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, nonanoic acid, CAS Registry Number 112-05-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4H-4a,9-methanoazuleno[5,6-d]-1,3-dioxole, octahydro-2,2,5,8,8,9a-hexamethyl-, (4aR,5R,7aS,9R)-, CAS Registry Number 211299-54-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, spiro[5.5]undec-8-en-1-one, 2,2,7,9-tetramethyl-, CAS Registry Number 502847-01-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, p-tolyl 3-methylcrotonate, CAS Registry Number 24700-20-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, hexanoic acid, CAS Registry Number 142-62-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methyl-4-phenyl-1,3-dioxolane, CAS Registry Number 33941-99-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-hydroxyacetophenone, CAS Registry Number CAS # 118-93-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4-isopropyl-2-methoxy-1-methylbenzene, CAS Registry Number 6379-73-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 1-ethynylcyclohexyl acetate, CAS Registry Number 5240-32-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4,4a,5,9b-tetrahydroindeno[1,2-d]-1,3-dioxine, CAS Registry Number 18096-62-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-phenyl-1-propanol, CAS Registry Number 122-97-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, benzaldehyde, CAS Registry Number 100-52-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, benzeneacetonitrile, a-butylidene-, (Z), CAS Registry Number 130786-09-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, geraniol, CAS registry number 106-24-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-phenoxyethanol, CAS Registry number 122-99-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, cinnamyl alcohol, CAS Registry Number 104-54-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, benzyl alcohol, CAS Registry Number 100-51-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, benzoic acid, 2-[[3-(4-methoxyphenyl)-2-methylpropylidene]amino]-, methyl ester, CAS registry number 111753-62-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

2nd update to RIFM fragrance ingredient safety assessment, 4-carvomenthenol, CAS Registry Number 562-74-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-tert-butylcyclohexyl acetate, CAS registry number 88-41-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-tert-butylcyclohexyl acetate, CAS Registry Number 31846-06-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4-tert-butylcyclohexyl acetate, CAS Registry Number 32210-23-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

P32-13 Outside the validated range: Performing a Weight of Evidence (WoE) assessment of the skin sensitization potential for fragrance chemicals positive at high concentrations only in the Local Lymph Node Assay (LLNA) - M. Lavelle; A. Natsch; I. Lee; I. Schember; V. Rocha; J. Muldoon; H. Moustakas; A.M. Api (Toxicology Letters, 2025)

RIFM fragrance ingredient safety assessment, phenyl salicylate, CAS Registry Number 118-55-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, fenchone, CAS Registry Number 1195-79-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, phenethyl acetate, CAS registry number 103-45-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, hydroxycitronellal diethyl acetal, CAS Registry Number 7779-94-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, amylcyclohexyl acetate (mixed isomers), CAS Registry Number 67874-72-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, octanal dimethyl acetal, CAS Registry Number 10022-28-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, linalyl hexanoate, CAS Registry Number 7779-23-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methylundecanal dimethyl acetal, CAS Registry Number 68141-17-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, hydroxycitronellal dimethyl acetal, CAS Registry number 141-92-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-isobutylquinoline, CAS registry number 93-19-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-methyl quinoline, CAS registry number 91-63-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 1,1-diethoxyisooctane, CAS Registry Number 69178-43-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, nonane, 1,1-diethoxy-, CAS Registry Number 54815-13-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1,1-diethoxy-3,5,5-trimethylhexane, CAS registry number 86198-35-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-(methylpropyl)quinoline, CAS registry number 1333-58-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, decanal dimethyl acetal, CAS Registry Number 7779-41-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4-isopropylphenol, CAS Registry Number 99-89-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 3-buten-2-one, 4-(2,2,3-trimethyl-6-methylenecyclohexyl)-, CAS registry number 79-68-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, heptanal dimethyl acetal, CAS registry number 10032-05-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 1,1-diethoxyhexane, CAS registry number 3658-93-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-acetyl-5-methylfuran, CAS Registry Number 1193-79-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isophytol, CAS Registry Number 505-32-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-furyl methyl ketone, CAS Registry Number 1192-62-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, savory winter oil, CAS Registry Number 90106-57-3, RIFM ID 1181-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM natural complex substance (NCS) fragrance ingredient safety assessment, ho wood oil, CAS Registry Number 8022-91-1, RIFM ID 217-D2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, dimethylcyclohex-3-ene-1-carbaldehyde (isomer unspecified), CAS Registry Number 27939-60-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 6-methyl-2-(4-methyl-3-cyclohexen-1-yl)-5-hepten-2-ol, CAS Registry Number 515-69-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, maltol, CAS registry number 118-71-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 3-(5,5,6-trimethylbicyclo[2.2.1]hept-2-yl)cyclohexan-1-ol, CAS registry number 3407-42-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, benzyl valerate, CAS Registry Number 10361-39-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isocyclocitral, CAS Registry Number 1335-66-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, ho leaf oil, CAS Registry Number 8022-91-1, RIFM ID 217-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM natural complex substance (NCS) fragrance ingredient safety assessment, ho bark oil, CAS registry number 8022-91-1, RIFM ID 217-C2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, benzyl formate, CAS Registry Number 104-57-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 1,1-diethoxyheptane, CAS Registry Number 688-82-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1-octanol, CAS registry number 111-87-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4,4a,6,7,8,8a-hexahydro-1,4-methanonaphthalen-5(1H)-one, CAS Registry Number 51519-65-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, amyl hexanoate, CAS registry number 540-07-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, undecanal, CAS Registry Number 112-44-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, N-benzoylanthranilic acid, CAS Registry Number 579-93-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, undecyl alcohol, CAS Registry Number 112-42-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1-tridecanol, CAS Registry Number 112-70-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, lauryl alcohol, CAS Registry Number 112-53-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, hexyl alcohol, CAS Registry Number 111-27-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, ethyl maltol, CAS Registry Number 4940-11-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, butyrophenone, CAS Registry Number 495-40-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, p-tolyl phenylacetate, CAS Registry Number 101-94-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, methyl decanoate, CAS Registry Number 110-42-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1-decanol, CAS registry number 112-30-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, clove bud absolute, CAS Registry Number 8000-34-8, RIFM ID 583-F2.1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, nonyl alcohol, CAS Registry Number 143-08-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, methoxy dicyclopentadiene carboxaldehyde, CAS Registry Number 86803-90-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, octahydro-4,7-methano-1H-indenecarbaldehyde, CAS Registry Number 30772-79-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, acetophenone, CAS Registry number 98-86-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, Sage oil, Spanish, CAS Registry Number 8022-56-8, RIFM ID 479-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

2nd Update to RIFM fragrance ingredient safety assessment, α-amylcinnamaldehyde, CAS Registry Number 122-40-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Corrigendum to “RIFM fragrance ingredient safety assessment, vanillin isobutyrate, CAS Registry Number 20665-85-4” [Food Chem. Toxicol. 197 Supplement 1 (2024) 115141 ISSN 0278–6915] - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, heptyl alcohol, CAS registry number 111-70-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4-acetoxy-2,5-dimethyl-3(2H)furanone, CAS Registry Number 4166-20-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isoamyl propionate, CAS Registry Number 105-68-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isobutyl propionate, CAS Registry Number 540-42-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4-(p-methoxyphenyl)-2-butanone, CAS Registry Number 104-20-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, cis-6-nonenal, CAS registry number 2277-19-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-phenylbutanal, CAS registry number 16251-77-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, cyclohexanepropanol, α-ethyl-2,2,6-trimethyl-, CAS Registry Number 60241-52-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, methyl 3,7-dimethyl-6-octenoate, CAS registry number 2270-60-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, (1aα,4α,7aα)-1a,3,3,4,6,6-hexamethyl-1a,2,3,4,5,6,7,7a-octahydronapth[3,3-b]oxirene, CAS Registry Number 94400-98-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, cyclododecyl formate, CAS Registry Number 59052-82-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, (Z)-4-dodecenal, CAS registry number 21944-98-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-phenylpropionaldehyde, CAS registry number 93-53-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4,5-dihydro-3(2H)thiophenone, CAS Registry Number 1003-04-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 9-undecenal, CAS Registry Number 143-14-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, β-methyl-benzenepentanal, CAS registry number 55066-49-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, nonanal, CAS registry number 124-19-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, trans-4-decen-1-al, CAS Registry Number 65405-70-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isoamyl formate, CAS Registry Number 110-45-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 8-undecenal, CAS registry number 58296-81-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, linalyl isovalerate, CAS Registry Number 1118-27-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, hexanal, CAS Registry Number 66-25-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4,8-dimethyl-7-nonen-2-ol, CAS Registry Number 40596-76-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-ethoxy-4-(methoxymethyl)phenol, CAS Registry Number 5595-79-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, β-caryophyllene alcohol, CAS registry number 472-97-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, acetylcarene, CAS Registry Number 3608-11-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4-heptenal, CAS Registry Number 6728-31-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isoamyl alcohol, CAS Registry Number 123-51-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-phenoxyethyl isobutyrate, CAS registry number 103-60-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, linalyl isobutyrate, CAS Registry Number 78-35-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1-tetradecanol, CAS Registry Number 112-72-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 3-hexenoic acid, CAS Registry Number 4219-24-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, methyl 2-nonynoate, CAS Registry Number 111-80-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 3-(4-methyl-3-cyclohexenyl)butanol, CAS Registry Number 15760-18-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, dihydro-β-ionol, CAS Registry Number 3293-47-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, p-tolylacetaldehyde, CAS Registry Number 104-09-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, β-pinene, CAS Registry Number 127-91-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, geranyl crotonate, CAS Registry Number 56172-46-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methyl-4(2,2,3-trimethyl-3-cyclopentenyl)butanol, CAS Registry Number 72089-08-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-methylbutyl valerate, CAS Registry Number 2050-09-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, octanal, CAS Registry Number 124-13-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, tricyclo[3.3.1.1.(3.7)]decan-2-ol, 4-methyl-8-methylene-, CAS Registry Number 122760-84-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, heptanal, CAS registry number 111-71-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methylbutyl butyrate, CAS Registry Number 51115-64-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, amyl alcohol, CAS Registry Number 71-41-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, pentanoic acid, 2-methylbutyl ester, CAS Registry Number 55590-83-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 3,4-xylenol, CAS Registry Number 95-65-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methylbutyl acetate, CAS Registry Number 624-41-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isobutyl butyrate, CAS Registry Number 539-90-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, decanal, CAS registry number 112-31-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, cedryl formate, CAS Registry Number 39900-38-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 4-(4-methoxyphenyl)-3-methylbutan-2-one, CAS Registry Number 67828-19-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1-(p-methoxyphenyl)-2-propanone, CAS Registry Number 122-84-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, trans-2-hexenyl acetate, CAS Registry Number 2497-18-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, isolongifolene oxide, CAS Registry Number 26619-69-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, p-menth-8-en-2-one, CAS Registry Number 7764-50-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, l-menthyl (R,S)-3-hydroxybutyrate, CAS Registry Number 108766-16-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, butyl alcohol, CAS registry number 71-36-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, tridecanal, CAS registry number 10486-19-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, cedr-8-ene epoxide, CAS Registry Number 13567-39-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, geranyl tiglate, CAS Registry Number 7785-33-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 4′-tert-butyl-2′,6′-dimethylacetophenone, CAS Registry Number 2040-10-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, ethyl trans-2,cis-4-decadienoate, CAS registry number 3025-30-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isoamyl acetate, CAS Registry Number 123-92-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1-hexadecanol, CAS Registry Number 36653-82-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isobutyl acetate, CAS Registry Number 110-19-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, cis-3-hexenyl salicylate, CAS Registry Number 65405-77-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methyl-2-hepten-6-ol, CAS registry number 1569-60-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, nopyl acetate, CAS registry number 128-51-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isoamyl butyrate, CAS Registry Number 106-27-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, piperonal, CAS Registry Number 120-57-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, benzothiazole, CAS Registry Number 95-16-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 1-cyclopropylmethyl-4-methoxybenzene, CAS registry number 16510-27-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 3,7-dimethyl-2-methylenocta-6-enal, CAS registry number 22418-66-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, isobutyl alcohol, CAS Registry Number 78-83-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 2-methylpropyl pentanoate, CAS Registry Number 10588-10-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, 2-(3-heptyl)-1,3-dioxolane, CAS Registry Number 4359-47-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, ethyl 2-methyl-3-pentenoate, CAS Registry Number 1617-23-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, vanillin isobutyrate, CAS Registry Number 20665-85-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2025)

Update to RIFM fragrance ingredient safety assessment, 3-methylbutanal diethyl acetal, CAS Registry Number 3842-03-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2025)

RIFM fragrance ingredient safety assessment, (4-methylphenoxy)acetaldehyde, CAS Registry Number 67845-46-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, propyl alcohol, CAS Registry Number 71-23-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, dibenzyl ether, CAS Registry number 103-50-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, β-ionyl acetate, CAS Registry Number 22030-19-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cinnamyl cinnamate, CAS Registry Number 122-69-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2,6-xylenol, CAS Registry Number 576-26-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isobutyl formate, CAS registry number 542-55-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methyl 2-octynoate, CAS Registry Number 111-12-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cyclohexanone 1,3-butylene glycol ketal, CAS Registry Number 6413-26-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, zingerone, CAS Registry Number 122-48-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-ethoxy-4-[(1-methylethoxy)methyl] phenol, CAS Registry number 96840-56-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, diethyl malonate, CAS registry number 105-53-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-(4,8-dimethylnona-3,7-dienyl)pyridine, CAS Registry Number 38462-23-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1,3-propanediol, 2,2-dimethyl-, 1,3-diacetate, CAS registry number 13431-57-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3-(cis-3-hexenyloxy)propanenitrile, CAS Registry Number 142653-61-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isobutyl benzoate, CAS registry number 120-50-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-(4-methyl-3-penten-1-yl)-2(5H)-furanone, CAS Registry number 61315-75-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M. Cronin; S. Crotty; M.L. Dagli; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-butyl-4,4,6-trimethyl-1,3-dioxane, CAS registry number 54546-26-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 1-(2-tert-butyl cyclohexyloxy)-2-butanol, CAS Registry Number 139504-68-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, ethyl 2-methylbutyrate, CAS Registry Number 7452-79-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, benzyl salicylate, CAS registry number 118-58-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, hexyl benzoate, CAS registry number 6789-88-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methyl isovalerate, CAS Registry Number 556-24-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, cyclohexanecarboxylic acid, CAS Registry Number 98-89-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, ethyl isobutyrate, CAS registry number 97-62-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 6,8-dimethylnonan-2-ol, CAS registry number 70214-77-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isoamyl benzoate, CAS registry number 94-46-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methyl isobutyrate, CAS registry number 547-63-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 10-undecenoic acid, heptyl ester, CAS registry number 68141-27-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3-(4-methylcyclohex-3-enyl)-3-butenyl acetate, CAS registry number 6819-19-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, p-methyl-α-amyl cinnamic aldehyde, CAS Registry Number 84697-09-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, methyl salicylate, CAS registry number 119-36-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methyl 2-methylbutyrate, CAS Registry Number 868-57-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, amyl salicylate, CAS Registry Number 2050-08-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 1-methyl-2-(1-methylpropyl)cyclohexyl acetate, CAS Registry number 72183-75-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cis-3-hexenyl benzoate, CAS Registry Number 25152-85-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isoamyl salicylate, CAS Registry Number 87-20-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 1-oxaspiro[4.5]decan-2-one, 8-(1-methylethyl)-, trans-, CAS Registry Number 4625-90-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-methyl-2-pentanol, CAS registry number 108-11-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2,6-dimethyl-4-heptanol, CAS registry number 108-82-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, heptyl acetate, CAS registry number 112-06-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Friedrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-methyl-5-phenylpentanol, CAS Registry Number 25634-93-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, hexyl formate, CAS registry number 629-33-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, hexyl butyrate, CAS Registry Number 2639-63-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, furfural, CAS Registry Number 98-01-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, octyl acetate, CAS Registry Number 112-14-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, octyl formate, CAS registry number 112-32-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 1-oxaspiro[4.5]decan-2-one, 8-ethyl-, trans-, CAS Registry Number 91069-40-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, p-mentha-1,8-dien-7-ol, CAS Registry Number 536-59-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 7-isopropyl-1,4-dimethylazulene, CAS registry number 489-84-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-isopropyl-1-methylcyclohexene, CAS registry number 29350-67-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, allyl α-ionone, CAS Registry Number 79-78-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, lauryl acetate, CAS Registry Number 112-66-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 1-oxaspiro[4.5]decan-2-one, 8-methyl-, CAS Registry number 94201-19-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-methyl-5-phenylpentanol, CAS Registry Number 55066-48-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, nonyl acetate, CAS registry number 143-13-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, octyl butyrate, CAS Registry Number 110-39-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-(methylthio)hexyl acetate, CAS registry number 51755-85-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2,2-dimethyl-3-phenylpropanol, CAS registry number 13351-61-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 5-(cis-3-hexenyl)dihydro-5-methyl-2(3H)furanone, CAS Registry Number 70851-61-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, o-phenyl anisole, CAS registry number 86-26-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, geranyl acetate, CAS registry number 105-87-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, geranyl linalool, CAS registry number 1113-21-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ionone (mixed isomers), CAS registry number 8013-90-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl salicylate, CAS Registry Number 118-61-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 4-phenyl-3-buten-2-ol, CAS registry number 17488-65-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isopropyl acetate, CAS registry number 108-21-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, hexyl propionate, CAS Registry Number 2445-76-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, α-butylcinnamaldehyde, CAS registry number 7492-44-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, decyl acetate, CAS Registry Number 112-17-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, musk ketone, CAS registry number 81-14-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, veratraldehyde, CAS Registry Number 120-14-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isopropyl butyrate, CAS Registry Number 638-11-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-hydroxybenzoic acid, CAS Registry Number 69-72-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 5-methylfurfural, CAS registry number 620-02-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, hexyl acetate, CAS registry number 142-92-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-methyl-4-phenylpentanol, CAS registry number 92585-24-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-methyl-4-phenylbutyraldehyde, CAS Registry Number 40654-82-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cis-3-hexenal, CAS Registry Number 6789-80-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, pinus nigra oil, CAS Registry Number 8000-26-8, RIFM ID 1068-E2.12 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cyclohexyl phenylacetate, CAS Registry Number 42288-75-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3,4,5,6,6-pentamethylheptan-2-ol, CAS registry number 87118-95-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1,3-cyclohexadiene-1-carboxylic acid, 4,6,6-trimethyl-, ethyl ester, CAS Registry Number 100520-15-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2(4H)-benzofuranone, 5,6-dihydro-3,6-dimethyl-, CAS Registry Number 80417-97-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, β-methylphenethyl alcohol, CAS Registry Number 1123-85-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, N-ethyl-N-(3-methylphenyl)propionamide, CAS Registry Number 179911-08-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, allyl cinnamate, CAS Registry number 1866-31-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-hexene, 1-[(2-methyl-2-propenyl)oxy]- (3Z)-, CAS Registry Number 292605-05-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM natural complex substance (NCS) fragrance ingredient safety assessment, lavandin abrialis, CAS registry number 8022-15-9, RIFM ID 1048554 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, rotundone, CAS Registry Number 18374-76-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methylheptenol, CAS Registry Number 1335-09-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1,4-bis(ethoxymethyl)cyclohexane, CAS Registry Number 54889-63-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, bicyclo[2.2.1]heptan-2-ol, 1,3,3-trimethyl-, benzoate, CAS Registry Number 55066-54-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-methylbutyl hexanoate, CAS registry Number 2601-13-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, propanoic acid, 2-methyl-, cyclohexyl ester, CAS Registry Number 1129-47-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3,7-dimethyl-1,6-nonadien-3-yl acetate, CAS Registry Number 61931-80-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-heptanol, 3,6-dimethyl-, CAS registry number 1247790-47-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl cyclohexanecarboxylate, CAS Registry Number 3289-28-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, linalyl butyrate, CAS Registry Number 78-36-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 6-butyl-2,4-dimethyldihydropyrane, CAS Registry Number 24237-00-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3,7-dimethyl-7-methoxyoctan-2-ol, CAS registry number 41890-92-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-isopropyl-N,2,3-trimethylbutyramide, CAS registry number 51115-67-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, piperonyl acetate, CAS registry number 326-61-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, α-propylphenethyl alcohol, CAS registry number 705-73-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, allyl heptanoate, CAS registry number 142-19-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-(4-methylphenoxy)ethanol, CAS Registry Number 15149-10-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, nonanoyl 4-hydroxy-3-methoxybenzylamide, CAS Registry Number 2444-46-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, allyl hexanoate, CAS Registry Number 123-68-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, phenethyl alcohol, CAS Registry Number 60-12-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, benzenepropanol, a,ß-dimethyl-, CAS Registry Number 56836-93-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-(2-oxopropyl)-2-pentylcyclopentanone, CAS Registry Number 40942-73-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 1,3,3-trimethyl-2-norbornanyl acetate, CAS registry number 13851-11-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, tetrahydrogeranial, CAS Registry Number 5988-91-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, isobornyl acetate, CAS Registry Number 125-12-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, nerolidyl acetate (isomer unspecified), CAS registry number 2306-78-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, oxacyclohexadecane-2,13-dione, CAS registry number 38223-29-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, (Z)-octadec-9-enol, CAS registry number 143-28-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, linalyl acetate, CAS registry number 115-95-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 1-naphthalenol, 1,2,3,4,4a,5,8,8a-octahydro-2,2,6,8-tetramethyl-, CAS Registry Number 103614-86-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3a,4,5,6,7,7a-hexahydro-4,7-methano-1H-inden-5-yl pivalate, CAS Registry Number 68039-45-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3a,4,5,6,7,7a-hexahydro-4,7-methano-1H-inden-5-yl isobutyrate, CAS Registry Number 67634-20-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, tricyclodecanyl acetate, CAS registry number 64001-15-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isobornyl propionate, CAS Registry Number 2756-56-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, allyl octanoate, CAS Registry Number 4230-97-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, linalyl formate, CAS registry number 115-99-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, nerol oxide, CAS Registry Number 1786-08-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, l-menthyl D-lactate, CAS registry number 59259-38-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, linalyl propionate, CAS registry number 144-39-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, trichloromethyl phenyl carbinyl acetate, CAS Registry number 90-17-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 4-hexen-1-ol, 5-methyl-2-(1-methylethenyl)-, CAS registry number 58461-27-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, dihydro-α-terpineol, CAS Registry Number 498-81-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-hexylcyclopentanone, CAS registry number 13074-65-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-methyl-4-phenyl-2-butyl isobutyrate, CAS registry number 10031-71-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, d,l-menthone 1,2-glycerol ketal, CAS Registry Number 63187-91-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 4-cyclohexyl-2-methyl-2-butanol, CAS registry number 83926-73-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4′-hydroxy-3′-methoxyacetophenone, CAS Registry Number 498-02-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2,2,4-trimethyl-4-phenyl-butane-nitrile, CAS Registry Number 75490-39-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, thymol, CAS Registry Number 89-83-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl cinnamate, CAS Registry Number 103-36-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-methyl-2-butenyl benzoate, CAS Registry Number 5205-11-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methylcyclooctyl carbonate, CAS Registry Number 61699-38-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-p-tolylethanol, CAS registry number 699-02-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3,7-dimethyl-1,3,6-octatriene, CAS Registry Number 13877-91-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1,1-dimethyl-2-phenylethyl isobutyrate, CAS Registry Number 59354-71-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, amyl cinnamate, CAS Registry Number 3487-99-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-methyl-4-phenyl-2-butanol, CAS Registry Number 103-05-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, benzenepropanenitrile, 4-ethyl-α,α.-dimethyl-, CAS Registry Number 134123-93-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, methyl 2,4-dihydroxy-m-toluate, CAS Registry Number 33662-58-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2H-1,5-benzodioxepin-3(4H)-one, 7-(1-methylethyl)-, CAS Registry Number 950919-28-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl 2-ethylhexanoate, CAS Registry Number 2983-37-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cyclohexyl salicylate, CAS registry number 25485-88-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment,α-methylbenzyl alcohol, CAS registry number 98-85-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-isopropylcyclohexanol, CAS Registry Number 4621-04-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, acetaldehyde, diphenethyl acetal, CAS Registry Number 122-71-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, α,α-dimethylphenethyl alcohol, CAS Registry Number 100-86-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, citronellyl ethyl oxalate, CAS Registry Number 60788-25-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, ethyl 2-tert-butylcyclohexyl carbonate, CAS Registry Number 67801-64-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, ethyl 2,3,6-trimethylcyclohexyl carbonate, CAS Registry Number 93981-50-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3-octyl acetate, CAS registry number 4864-61-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, exo-2-[(1,7,7-trimethylbicyclo[2.2.1]hept-2-yl)oxy]ethanol, CAS Registry Number 7070-15-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-propanol, reaction products with boron trifluoride and 5-ethylidenebicyclo[2.2.1]hept-2-ene, CAS registry number 90530-04-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1-propanol, 2-methyl-3-[(1,7,7-trimethylbicyclo-[2.2.1]hept-2-yl)oxy]-, CAS Registry Number 128119-70-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1,3-nonanediol acetate (mixed esters), CAS Registry Number 1322-17-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3,12-tridecadienenitrile, CAS Registry Number 134769-33-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, hexanoic acid, 4-methyl-, CAS registry number 1561-11-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 4-ethyloctanoic acid, CAS registry number 16493-80-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-methylhexanoic acid, CAS registry number 4536-23-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-methylheptanoic acid, CAS registry number 1188-02-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, butyl 2-methylvalerate, CAS Registry Number 6297-41-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, N,N-diethyloctamide, CAS registry number 996-97-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, phenethyl salicylate, CAS Registry Number 87-22-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, benzonitrile, 3,4-dimethyl-, CAS Registry Number 22884-95-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-allyl-2-methoxyphenyl benzyl ether, CAS Registry Number 57371-42-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3,6-nonadien-1-ol, CAS Registry Number 76649-25-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl 2-methylpentanoate, CAS Registry Number 39255-32-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, linalyl cinnamate, CAS registry number 78-37-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl 3,5,5-trimethylhexanoate, CAS Registry Number 67707-75-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 4-methyloctanoic acid, CAS Registry Number 54947-74-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, butyl 10-undecenoate, CAS Registry Number 109-42-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-methylvaleric acid, CAS Registry Number 97-61-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3-methylpentanoic acid, CAS registry number 105-43-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 4-methylnonanoic acid, CAS Registry Number 45019-28-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-ethylbutyric acid, CAS Registry Number 88-09-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cis- and trans-p-1(7),8-menthadien-2-yl acetate, CAS registry number 71660-03-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, diethyldimethylcyclohex-2-en-1-one, CAS Registry Number 68845-36-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-phenyl-3-buten-1-yl acetate, CAS Registry Number 7306-12-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, spiro[1,3-dioxolane-2,8′(5′H)-[2H-2,4a]methanonaphthalene],hexahydro-1′,1′,5′,5′-tetramethyl-, [2′S-(2′α,4′aα,8′aα)]-, CAS Registry Number 154171-77-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, p-tolyl alcohol, CAS Registry Number 589-18-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 4-methylpentanoic acid, CAS Registry Number 646-07-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 5-ethyl-2,3,4,5-tetramethylcyclohexen-1-one, CAS Registry Number 17369-60-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cyclohexanol, 2-methoxy-4-propyl-, CAS Registry Number 23950-98-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, ethyl 10-undecenoate, CAS Registry Number 692-86-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, p-tert-butyldihydrocinnamaldehyde, CAS Registry Number 18127-01-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, isoeugenyl phenylacetate, CAS registry number 120-24-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, menthyl acetate (isomer unspecified), CAS registry number 16409-45-3 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM natural complex substance (NCS) fragrance ingredient safety assessment, Mandarin oil terpenes, CAS registry number 68953-04-8, RIFM ID 250-G2.30 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, orange essence oil, CAS Registry Number 68514-75-0, RIFM ID 192-G2.10 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM Natural Complex Substance (NCS) fragrance ingredient safety assessment, tangelo oil, expressed, CAS Registry Number 72869-73-9, RIFM ID 931-G2.5 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-(p-isopropylphenyl)propionaldehyde, CAS registry number 7775-00-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3,3,5-trimethylcyclohexyl ethyl ether, CAS Registry Number 67583-77-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, triethyltrimethyl-2-cyclohexen-1-one, CAS Registry Number 68845-35-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, methyl vanillate, CAS Registry Number 3943-74-6 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, germacrene D, CAS Registry Number 23986-74-5 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 5-methyl-2-thiophenecarboxaldehyde, CAS registry number 13679-70-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, isoeugenyl benzyl ether, CAS Registry Number 120-11-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, pentyl benzoate, CAS Registry Number 2049-96-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl vanillin isobutyrate, CAS Registry Number 188417-26-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, l-carvone, CAS Registry Number 6485-40-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, butyl benzoate, CAS Registry Number 136-60-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, p-isopropyl phenylacetaldehyde, CAS Registry Number 4395-92-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methyl benzoate, CAS Registry Number 93-58-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cyclohexane, 1-(1,1-dimethylpropyl)-4-ethoxy-, cis-, CAS Registry Number 181258-87-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-methyl-3-decen-5-ol, CAS Registry Number 81782-77-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, isoeugenol, CAS registry number 97-54-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 10-undecen-1-yl acetate, CAS Registry Number 112-19-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-methyl-2-pentenoic acid, CAS Registry Number 16957-70-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 6,10-dodecadienal, 3,7,11-trimethyl-, (3S,6E)-, CAS registry number 194934-66-2 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, cuminyl nitrile, CAS registry number 13816-33-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, (Z,Z)-1,1'-[ethylidenebis(oxy)]di(hex-3-ene), CAS Registry number 63449-64-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, ethyl benzoate, CAS Registry Number 93-89-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 5-methyl-5-phenyl-3-hexanone, CAS Registry Number 4927-36-0 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, (E)-1-(1-methoxypropoxy)hex-3-ene, CAS Registry Number 97358-54-8 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methyl undec-10-enoate, CAS registry number 111-81-9 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, acetaldehyde ethyl cis-3-hexenyl acetal, CAS Registry Number 28069-74-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, α-amylcinnamaldehyde, CAS Registry Number 122-40-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 9-decenyl acetate, CAS Registry Number 50816-18-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, terpinyl acetate (isomer mixture), CAS Registry Number 8007-35-0 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, butyric acid, CAS Registry Number 107-92-6 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, phenol, 4-(3,6-dihydro-4-methyl-2H-pyran-2-yl)-2-methoxy-, CAS Registry Number 128489-02-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, eucalyptol, CAS Registry Number 470-82-6 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 7-methyl-2H-benzo-1,5-dioxepin-3(4H)-one, CAS Registry Number 28940-11-6 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, santalol, CAS Registry Number 11031-45-1 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, o-methoxybenzaldehyde, CAS Registry Number 135-02-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-(isopropyl)cyclohexyl propionate, CAS Registry Number 63449-95-6 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, dextro-verbenone, CAS Registry Number 18309-32-5 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, pyridine, 5-hexyl-2-methyl-, CAS Registry Number 710-40-7 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, dodecahydro-3,8,8,11a-tetramethyl-5H-3,5a-epoxynaphth[2,1-c]oxepin, CAS Registry Number 57345-19-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-pentylcyclopentan-1-one, CAS Registry Number 4819-67-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-methyl-4-phenyl-2-butyl acetate, CAS Registry Number 103-07-1 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-methyl-3-buten-2-ol, CAS Registry Number 115-18-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 3,7-dimethyl-6-octenoic acid, CAS Registry Number 502-47-6 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-methyl-4-phenyl-2-pentanone, CAS Registry Number 7403-42-1 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl 2,4,7-decatrienoate, CAS Registry Number 78417-28-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2(3H)-benzofuranone, hexahydro-3,6-dimethyl-, CAS Registry Number 92015-65-1 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 5-ethylidenebicyclo[2.2.1]hept-2-yl propionate, CAS Registry Number 73347-77-0 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, o-toluenethiol, CAS Registry Number 137-06-4 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, benzoic acid, 2-hydroxy-5-methyl-, methyl ester, CAS Registry Number 22717-57-3 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-acetoxy-3-ethoxybenzaldehyde, CAS Registry Number 72207-94-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, anisyl acetate (isomer unspecified), CAS Registry Number 1331-83-5 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 5-methylquinoxaline, CAS Registry Number 13708-12-8 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, terpinyl formate, CAS Registry Number 2153-26-6 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-isobutyl-3-methoxypyrazine, CAS registry number 24683-00-9 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3,5-heptadien-1-ol, 1-acetate, (3Z,5E)-, CAS Registry Number 86611-09-8 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, acetic acid, CAS Registry Number 64-19-7 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, isopropoxy ethyl salicylate, CAS Registry Number 79915-74-5 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl 2-methoxybenzoate, CAS Registry Number 7335-26-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, β-phellandrene, CAS Registry Number 555-10-2 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1-oxaspiro[4.5]deca-3,6-diene, 2,6,9,10-tetramethyl-, CAS Registry Number 71078-31-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2,4,5-trimethylthiazole, CAS Registry Number 13623-11-5 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, propionic acid, CAS Registry Number 79-09-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2-methyl-3,5 or 6-ethoxypyrazine, CAS Registry Number 32737-14-7 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1,3-benzodioxole, 5-(diethoxymethyl)-, CAS Registry Number 40527-42-2 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, methyl phenylacetate, CAS Registry Number 101-41-7 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, methyl o-methoxybenzoate, CAS registry number 606-45-1 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, citral propylene glycol acetal, CAS Registry number 10444-50-5 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, (E)-2-phenylpropenyl acetate, CAS registry number 37973-51-6 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ethyl benzoylacetate, CAS registry number 94-02-0 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, pyridine, 4-[1(4-,5 or 6)-methylbicyclo[2.2.1]hept-5-en-2-yl]-, CAS Registry Number 862079-91-2 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1,3,5-undecatriene, CAS Registry Number 16356-11-9 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, hexahydro-3H-benzofuran-2-one, CAS Registry Number 6051-03-2 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, (3-methoxy-2-methylpropyl)benzene, CAS Registry Number 120811-92-9 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2-heptylcyclopentanone, CAS Registry Number 137-03-1 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 2,4,4,7-tetramethylnona-6,8-diene-3-one-oxime, CAS Registry Number 81783-01-9 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, acetaldehyde ethyl linalyl acetal, CAS Registry Number 40910-49-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, pentyl phenylacetate, CAS Registry Number 5137-52-0 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cinnamyl nitrile, CAS Registry Number 1885-38-7 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, carvacrol, CAS Registry Number 499-75-2 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 5- and 6-decenoic acid, CAS Registry Number 72881-27-7 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 2H-inden-2-one, 1,3-dihydro-, CAS Registry Number 615-13-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, hydroxycitronellol, CAS Registry Number 107-74-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, formic acid, CAS Registry number 64-18-6 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, 1-octen-3-ol, CAS Registry Number 3391-86-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, linalool oxide, CAS Registry Number 1365-19-1 - A.M. Api; A. Bartlett; D. Belsito; D. Botelho; M. Bruze; A. Bryant-Freidrich; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 1,3-dimethyl-3-phenylbutyl acetate, CAS Registry Number 68083-58-9 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, anisyl formate, CAS registry number 122-91-8 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3-ethyl-2,6-dimethylpyrazine, CAS Registry Number 13925-07-0 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, (1R,2S,5R)-N-(4-methoxyphenyl)-5-methyl-2-(1-methylethyl)cyclohexanecarboxamide, CAS Registry Number 68489-09-8 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, benzoic acid, 2-[(2-phenylethylidene)amino]-, methyl ester, CAS Registry Number 67785-76-6 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, butyl salicylate, CAS Registry Number 2052-14-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, cycloionone, CAS Registry Number 5552-30-7 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

Update to RIFM fragrance ingredient safety assessment, ethyl phenylacetate, CAS Registry Number 101-97-3 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 4-tert-butylcyclohexanol, CAS Registry Number 98-52-2 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, α,α-dimethylphenylethyl propionate, CAS Registry Number 67785-77-7 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, β-ionol, CAS Registry Number 22029-76-1 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, hexyl salicylate, CAS Registry Number 6259-76-3 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, ocimenol, CAS Registry Number 5986-38-9 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 3,4-dihydro-5-methylnaphthalen-1(2H)-one, CAS Registry Number 6939-35-1 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, 5-ethyl-3-hydroxy-4-methyl-2(5H)-furanone, CAS Registry Number 698-10-2 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2024)

RIFM fragrance ingredient safety assessment, benzene, 1-(dimethoxymethyl)-4-methoxy-, CAS Registry Number 2186-92-7 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

Update to RIFM fragrance ingredient safety assessment, α-isobutylphenethyl alcohol, CAS Registry Number 7779-78-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, anisyl propionate, CAS Registry Number 7549-33-9 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

Update to RIFM fragrance ingredient safety assessment, tetrahydro-4-methyl-2-(2-methylpropen-1-yl)pyran, CAS Registry Number 16409-43-1 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, camphene, CAS Registry Number 79-92-5 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, salicylaldehyde, CAS Registry Number 90-02-8 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 2-methoxy-3-methylpyrazine, CAS Registry Number 2847-30-5 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, N-p-benzeneacetonitrilementhanecarboxamide, CAS Registry Number 852379-28-3 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

Update to RIFM fragrance ingredient safety assessment, dimethyl succinate, CAS Registry Number 106-65-0 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 1-methylnaphthalene, CAS Registry Number 90-12-0 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 5-hydroxy-2,4-decadienoic acid δ-lactone, CAS Registry Number 27593-23-3 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

Update to RIFM fragrance ingredient safety assessment, trans-2-hexenoic acid, CAS Registry Number 13419-69-7 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

Update to RIFM fragrance ingredient safety assessment, acetaldehyde ethyl phenylethyl acetal, CAS Registry Number 2556-10-7 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 2,4,6-cycloheptatrien-1-one, 2-hydroxy-4-(1-methylethyl)-, CAS Registry Number 499-44-5 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

Update to RIFM fragrance ingredient safety assessment, ethylene dodecanedioate, CAS Registry Number 54982-83-1 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

Update to RIFM fragrance ingredient safety assessment, 2,2,5-trimethyl-5-pentylcyclopentanone, CAS Registry Number 65443-14-3 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, benzoic acid, 2-hydroxy-, 2-methylbutyl ester, CAS Registry Number 51115-63-0 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, α,α-dimethylphenethyl butyrate, CAS Registry Number 10094-34-5 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

Update to RIFM fragrance ingredient safety assessment, isoamyl hexanoate, CAS registry number 2198-61-0 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

Update to RIFM fragrance ingredient safety assessment, ethyl 3-phenylpropionate, CAS Registry Number 2021-28-5 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 1,1-dimethyl-2-phenylethyl acetate, CAS registry number 151-05-3 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 1,5,7-octatrien-3-ol, 3,7-dimethyl-, (5E)-, CAS Registry Number 53834-70-1 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, tetrahydro-4-methyl-2-phenyl-2H-pyran, CAS Registry Number 94201-73-7 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

Update to RIFM fragrance ingredient safety assessment, linalyl benzoate, CAS Registry Number 126-64-7 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

Update to RIFM fragrance ingredient safety assessment, butyl phenylacetate, CAS Registry Number 122-43-0 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

Update to RIFM fragrance ingredient safety assessment, 3-ethylhexahydro-2(3H)-benzofuranone, CAS Registry Number 54491-17-7 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 4,5-dimethyl-3-hydroxy-2,5-dihydrofuran-2-one, CAS Registry Number 28664-35-9 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, l-lactic acid (2-hydroxy propionic acid), CAS Registry Number 79-33-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, dihydronootkatone, CAS Registry Number 20489-53-6 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 9-hexadecyn-8-one, CAS Registry Number 89319-68-6 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, yuzunone, CAS Registry Number 1009814-14-5 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 4-methoxybenzaldehyde diethyl acetal, CAS Registry Number 2403-58-9 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, estragole, CAS registry number 140-67-0 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, methoxypyrazine, CAS registry number 3149-28-8 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

Update to RIFM fragrance ingredient safety assessment, myrcenol, CAS Registry Number 543-39-5 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

Update to RIFM fragrance ingredient safety assessment, diethyl succinate, CAS Registry Number 123-25-1 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, isobutyl salicylate, CAS Registry Number 87-19-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

Update to RIFM fragrance ingredient safety assessment, propyl phenethyl acetal, CAS registry number 7493-57-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 2-phenylhexanenitrile, CAS registry number 3508-98-3 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 2-methyl-3-(1-oxopropoxy)-4H-pyran-4-one, CAS Registry Number 68555-63-5 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, ethyl p-anisate, CAS registry number 94-30-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 4-hydroxybenzaldehyde, CAS registry number 123-08-0 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

Update to RIFM fragrance ingredient safety assessment, isoamyl octanoate, CAS registry number 2035-99-6 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 2,3,3-trimethylindanone, CAS registry number 54440-17-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

RIFM fragrance ingredient safety assessment, 2-methoxy-3(5 and 6)-isopropylpyrazine, CAS Registry Number 25773-40-4 - A.M. Api; D. Belsito; D. Botelho; M. Bruze; G.A. Burton; M.A. Cancellieri; H. Chon; M.L. Dagli; W. Dekant; C. Deodhar; A.D. Fryer; L. Jones; et al. (Food and Chemical Toxicology, 2023)

Invasive pulmonary aspergillosis is associated with adverse clinical outcomes in critically ill patients receiving veno-venous extracorporeal membrane oxygenation - I. Rodriguez-Goncer; S. Thomas; P. Foden; M. D. Richardson; A. Ashworth; J. Barker; C. G. Geraghty; E. G. Muldoon; T. W. Felton (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Predation on Subfossil Prolemur simus by Multiple Predator Species at Ankarana Massif, Northern Madagascar - Kathleen M. Muldoon; Laurie R. Godfrey; Brooke E. Crowley; Elwyn L. Simons (International Journal of Primatology, 2017)

Steven M. Goodman and William L. Jungers: Extinct Madagascar: Picturing the Island’s Past - Kathleen M. Muldoon (International Journal of Primatology, 2016)

Outpatient parenteral antimicrobial therapy (OPAT) in the republic of Ireland: results of a national survey - E. G. Muldoon; G. M. Allison; D. Gallagher; D. R. Snydman; C. Bergin (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

The cannabinoid CB2 receptor is necessary for nicotine-conditioned place preference, but not other behavioral effects of nicotine in mice - Bogna M. Ignatowska-Jankowska; Pretal P. Muldoon; Aron H. Lichtman; M. Imad Damaj (Psychopharmacology, 2013)

Genetic polymorphisms associated with exertional rhabdomyolysis - Patricia A. Deuster; Carmen L. Contreras-Sesvold; Francis G. O’Connor; William W. Campbell; Kimbra Kenney; John F. Capacchione; Mark E. Landau; Sheila M. Muldoon; Elisabeth J. Rushing; Yuval Heled (European Journal of Applied Physiology, 2013)

Clinical correlation and molecular evaluation confirm that the MLH1 p.Arg182Gly (c.544A>G) mutation is pathogenic and causes Lynch syndrome - Michael P. Farrell; David J. Hughes; Ian R. Berry; David J. Gallagher; Emily A. Glogowski; Stewart J. Payne; Michael J. Kennedy; Róisín M. Clarke; Susan A. White; Cian B. Muldoon; Fiona Macdonald; Pauline Rehal; et al. (Familial Cancer, 2012)

Ecological biogeography of Malagasy non‐volant mammals: community structure is correlated with habitat - Kathleen M. Muldoon; Steven M. Goodman (Journal of Biogeography, 2010)
Aim To examine the relationship between ecoregions, as a proxy for regional climate and habitat type, and mammalian community structure, defined by species composition and richness (e.g. taxonomic structure) and ecological diversity (e.g. ecological structure) of non‐volant species. Location Madagascar. Methods Faunal lists of non‐volant mammal species occurring in 35 communities from five World Wildlife Fund ecoregions were collected from published and unpublished sources. Species were assigned to ecological groups defined by trophic status, locomotor habits, activity cycle and body mass. We used Mantel tests, cluster analysis and principal coordinates analysis to evaluate geographic patterning in taxonomic composition and species richness. We used stepwise multiple discriminant analysis to characterize patterns in the ecological diversity of the mammalian communities from each ecoregion. Communities from transitional habitats (e.g. representing more than one ecoregion) were used to test the predictive power of the analyses. Results Non‐volant mammal communities divided into clusters that correspond to ecoregions. There was a strong distance effect in the taxonomic structure of communities across the island and within both humid and dry forest communities, but this effect was weak within humid forest communities. Mammalian species richness was significantly lower in dry forest than in humid forest communities. The ecological structure of communities was also correlated with ecoregions. Changes in the relative percentages of omnivory, arboreal quadrupedalism, terrestrial/arboreal quadrupedalism and two body mass classes accounted for 98.1% of the variation in ecological structure. Transitional communities were projected in intermediate positions by the discriminant model. Main conclusions Our analysis demonstrates that the broad‐scale habitat and climate variables captured by the ecoregion model have shaped the assembly of non‐volant mammal communities in Madagascar over evolutionary time. The spatial pattern is consistent with ecological sorting of species ranges along environmental gradients. Historical processes, such as recent extinction and migration, may have also affected the structure of mammal communities, although these factors have played a secondary role.

Correlation of hydraulic conductivity with stratigraphy in a fractured-dolomite aquifer, northeastern Wisconsin, USA - Muldoon M.; J. (Toni) Simo; Bradbury K. (Hydrogeology Journal, 2001)

Enchytraeids and nematophagous fungi in soil microcosms - B. A. Jaffee; A. E. Muldoon; W. A. M. Didden (Biology and Fertility of Soils, 1997)